Mental health well being and economic struggles of unorganized women workers: A cross-sectional study - Dayana, S. Mary; Sebastine, Anand Jerard (Edelweiss Applied Science and Technology, 2025)
Globally, unorganized women workers are experience informal work settings without the support of legal entities. The present study investigated the Mental Health and Economic Struggles faced by unorganized women workers in the coir processing and seafood industries in the southern coastal region of India. This study aims to examine the Mental Health Well beings and economic challenges faced by unorganized fisherwomen workers in the Thanjavur District of Tamil Nadu through a cross-sectional survey. A total of 500 women aged 18 years and above, engaged in informal labour, were included in the study. A multistage random sampling technique ensured representation from rural, semi-urban, and urban areas. Primary data were collected using a self-prepared questionnaire addressing socio-demographic details, economic challenges, and psychosocial problems, including the perceived stress scale. Data were analysed using SPSS. The average age of participants was 43.7 years, with the majority (44.4%) falling within the 40-50 years age group. Most participants earned between ₹4000-₹5000 (51.2%), worked seasonally (83.4%), and spent an average of 7.5 hours per day on work, with 59% working more than 10 hours. Over half (58.4%) reported insufficient lunchtime, which could affect their well-being. A significant relationship (p<0.001) was found between age (40-50 years) and high stress levels. The study revealed that receiving extra wages was associated with increased stress (p<0.001). Factor analysis identified four key components of psychosocial stress: 1) Emotional Distress, 2) Positive Outlook, 3) Personal Mastery, and 4) Coping Challenges. The study concludes with policy recommendations aimed at improving the socio-economic conditions and overall well-being of unorganized fisherwomen workers.